1,3-Benzyl migration in iminium ions: evidence for a fast free-radical chain reaction - Blank, Nancy; Straub, Bernd Franz; Opatz, Till (European journal of organic chemistry, 2011)
The “exocyclic” 1,3-benzyl shift observed in iminium salts derived from 1-benzyl-1,2,3,4-tetrahydroisoquinolines is related to the “endocyclic” Knabe rearrangement. A crossover experiment, isotopic labelling, the study of initiators and inhibitors as well as DFT calculations of gas-phase model structures provide evidence for a free-radical pathway under kinetic entropy control that is not affected by “slow” radical traps.